Three stage maturity model in SME's toward industry 4.0 - Jaione Ganzarain; Nekane Errasti (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: To address the challenges regarding the concept of Industry 4.0 and the diversification methodology and based on the strategic guidance towards Industry 4.0, we propose a process model as a guiding framework for Industry 4.0 collaborative diversification vision, strategy and action building. In this paper we suggest a stage process model to guide and train companies to identify new opportunities for diversification within Industry 4.0. Systematically carrying out the stages will take a company to their individual specific vision and collaborative vision between different companies in the Industry 4.0 scenario. Design/methodology/approach: This new collaborative diversification methodology involves industry within the pilot program; from the diversification and capacity assessment analysis of the company`s profile, skills and technologies that dominates, to identify the diversification opportunity map and its business modeling within the Industry 4.0 paradigm. Findings: The application of maturity models to the Industry 4.0 may help organizations to integrate this methodology into their culture. Results show a real need for guided support in developing a company-specific Industry 4.0 vision and specific project planning. Originality/value: Industry 4.0 promotes a vision where recent developments in information technology are expected to enable entirely new forms of cooperative engineering and manufacturing. The vision of industry 4.0 describes a whole new approach to business operations, and especially the production industries. To address the challenges regarding the concept of Industry 4.0 and the diversification methodology discussed above, and based on the strategic guidance towards Industry 4.0, we propose a unique process model as a guiding framework for Industry 4.0 collaborative diversification vision, strategy and action building.
Keywords: 650; SMEs; university-industry collaboration; industry 4.0; diversification strategy; maturity model